Welding Modern Topics - Crisóstomo Absi Alfaro, Sadek; Borek, Wojciech; Tomiczek, Błażej (IntechOpen, 2021)
The welding process is used by manufacturing companies worldwide. Due to this broad application, many studies have been carried out in various fields to improve the quality and reduce the cost of welded components and structures. Welding is a complex and non-linear physical and mechanistic process. This book relates the importance of automation and control in welding processes, highlights some modern processes, and shows, among other influential welding factors, the importance of metal thermomechanical processing studies.